Identification of a Malaysian tiger milk mushroom specimen and characterisation of its mycelial (1,3)-β-D-Glucan / Siti Rokhiyah Ahmad Usuldin - Siti Rokhiyah, Ahmad Usuldin (2020)
The tiger milk mushroom (Lignosus rhinocerus) is an important medicinal mushroom and regarded as Malaysia national heritage. Its sclerotia (tuber) has been consumed by the indigenous community (Orang Asli) to treat illnesses such as asthma, fever, cough, cancer and other diseases. The mushroom is rare and difficult to find in nature and has frequently been confused with another mushroom of similar anatomy. Traditionally, the cultivation of the sclerotium takes a long time and propagation of its mycelial biomass and exopolysaccharides (EPS) in a stirred-tank bioreactor is an excellent alternative technique. The present study aimed to identify the wild-Malaysian tiger milk mushroom and characterise the extracted EPS from its mycelial culture in a stirred-tank bioreactor. The mushroom was morphologically identified based on its pileus, stipe and sclerotium. The extracted fungal DNA was sequenced and found to have 99% similar to L. rhinocerus strains CH31 and CH2. Phylogenetically, evolutionary distance (Knuc) and plasmid-matching software (ApE) for sequences of matching fungal species verified that the isolate belonged to the L. rhinocerus species and warranted as Lignosus rhinocerus strain ABI (LRSA). The strain was cultured in a 13 L stirred-tank Labfors, Infors-HT bioreactor and its mycelial β-glucan (G) was extracted for compound characterisation. The structure of EPS was studied using Fourier-Transform Infrared Spectroscopy (FT-IR) and one-dimensional (1D) and two-dimensional (2D) Nuclear Magnetic Resonance (NMR). FT-IR spectroscopy showed that G exhibited a similar β-glycosidic structure to the standard (laminarin) and the presence of characteristic bands at 3277, 2919, 1638, 1545, 1400, 1078 and 896 cm-1 confirmed the similarities. 1H and 13C NMR, as well as 2D NMR: homonuclear correlation spectroscopy (COSY), total correlation spectroscopy (TOCSY), heteronuclear multiple quantum coherence (HMQC) and heteronuclear multiple bond coherence (HMBC) spectra, were used for structural elucidation of the β-glucan and confirmed the extracted material as (1,3)-β-D-glucan. These findings may facilitate the development of G production in a high-scale bioreactor using LRSA.